Preliminary results of curettage and cementation in the treatment of fibrous dysplasia of the proximal radius - Badr, Ismail Tawfeek; Lekhraj Rampal, Sanjiv Rampal; Shahin, Ahmed (Indian Orthopaedic Research Group, 2019)
Introduction: Fibrous dysplasia (FD)is a benign pathological condition usually observed in the first three decades of life. A single bone may be involved either wholly or partially, or multiple bones may be affected, we aimed to use curettage and cementation as a control method of FDfibrous dysplasia of the proximal radius. Methods: We describe our finding with the treatment of FDfibrous dysplasia of the proximal radius in five patients(four females and, one male), the mean age of 28.6 years (22 to –39 years). The lesions were in the metaphysis extending to the diaphysis. Persistent pain and pain after pathological fracture were the indications for surgical intervention. We used an extensile approach to expose the lesion then extended curettage using a high-speed burr and filling the cavity with bone cement. Functional outcome and radiological findings were monitored on follow-up visits. Results: The mean follow-up period was 3.2 years (ranged from 2 years to 5 years).There was were no recurrences and no patient sustained a fracture at the end of the filling cement. At the time of the last follow-up, all patients have excellent score(mean 27 points) according to the musculoskeletal tumor society scoring system. Conclusion: Extended curettage and cementation provide a safe and reliable alternative for control of FDfibrous dysplasia of the proximal radius with little morbidity with little risk of recurrence and low incidence of complications.